2009
DOI: 10.1007/s11655-009-0448-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorophytum Borivilianum Santapau and Fernandes on sexual dysfunction in hyperglycemic male rats

Abstract: CB can significantly ameliorate diabetes-induced sexual dysfunction. Polysaccharide and saponin-rich aqueous extract appears to have the most suitable effects on diabetes and its associated effects on sexual functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Similarly, Thakur et al (2009) have reported a decrease in apoptosis of spermatozoa of T1 diabetic rats following 28 days administration of Chlorophytum borivilianum root extract. In addition, the activity of caspase-3 in the spermatozoa is significantly decreased compared to the diabetic untreated rats (Thakur et al, 2009). Studies using phenolic compounds have also yielded a similar trend of results.…”
Section: Natural Products With Testicular Effects In Diabetes Mellitusmentioning
confidence: 76%
See 2 more Smart Citations
“…Similarly, Thakur et al (2009) have reported a decrease in apoptosis of spermatozoa of T1 diabetic rats following 28 days administration of Chlorophytum borivilianum root extract. In addition, the activity of caspase-3 in the spermatozoa is significantly decreased compared to the diabetic untreated rats (Thakur et al, 2009). Studies using phenolic compounds have also yielded a similar trend of results.…”
Section: Natural Products With Testicular Effects In Diabetes Mellitusmentioning
confidence: 76%
“…Glibenclamide ↓# ↑ Sperm count, motility, viability and % normal morphology; ↓ oxidative stress and apoptosis in sperm (Thakur et al, 2009 (Khaki et al, 2014).…”
Section: Natural Products and Dm-induced Impairment In Male Reproductmentioning
confidence: 99%
See 1 more Smart Citation
“…12,18 Although it is reported that STZ treatment reduced plasma T levels in rats, this factor alone does not appear responsible for changes in copulatory behavior as T replacement did not reverse the adverse effects of diabetes on sexual behavior. 26 Although STZ-induced copulatory dysfunction might be due to reduced T responsiveness, copulatory dysfunction in the diabetic state is also a result of direct or indirect action of insulin and/or glucose on the adrenergic complex.…”
Section: Discussionmentioning
confidence: 99%
“…Mount and intromission latency, which was calculated as the time from the introduction of female to the occurrence of first mount and intromission, respectively. 18 Post ejaculatory interval was calculated as time from ejaculation until next intromission. Other principle parameters determined in this study were mount, intromission and ejaculatory frequencies.…”
Section: Collection Extraction and Characterizationmentioning
confidence: 99%